Approximations of ∈, ∈∨qk-Fuzzy Hyperideals in Ordered LA-Semihypergroups. (7th May 2021) - Abughazalah, Nabilah; Yaqoob, Naveed; Ashraf, Samavia
Abstract : This paper concerns the relationship between rough sets, ∈, ∈ ∨ q k -fuzzy sets, and the LA-semihypergroups. We proved that the lower approximation (l -approx) and the upper approximation (u -approx) of different hyperideals of LA-semihypergroups become again hyperideal and also provided some examples. We also provided a result which shows that, if ϑ is not a hyperideal of an LA-semihypergroup P, then its lower approximation is also not a hyperideal.